Better English pronunciation - O'Connor, J. D. (Cambridge : New York : Cambridge University Press, 2005)
A systematic and thorough introduction to the pronunciation of English for use by intermediate and more advanced students.
Includes glossary.
Keywords: English language -- Textbooks for foreign speakers; English language -- Pronunciation -- Problems, exercises, etc